Association between lung function and future risks of diabetes, asthma, myocardial infarction, hypertension and all-cause mortality. Issue 3 (20th September 2021) - Shah, Chintal H.; Reed, Robert M.; Liang, Yulan; Zafari, Zafar
Background: While forced expiratory volume in 1 s (FEV1 ) is a hallmark of disease progression in chronic obstructive lung diseases, little is known about the relationship between baseline FEV1 and future risks of other medical conditions. Objective: The aim of this study was to investigate the association between baseline FEV1 and future risks of diabetes, asthma, myocardial infarction, hypertension and all-cause mortality. Methods: We used data from the National Health and Nutrition Examination Survey and its Epidemiological Follow-Up Study. Our data provided longitudinal follow-up of the original cohort for up to 12 years. We used two competing risks approaches, the cause-specific hazard model and the Fine–Gray sub-distribution hazard model, to measure the associations between baseline FEV1 and future risks of the outcomes of interest. All models were adjusted for major confounding factors. Results: The final sample included 3020 participants (mean±sd baseline age 44.64±13.44 years). In the cause-specific hazard model, for every per cent increase in the baseline per cent predicted FEV1, the hazard of the event reduced by 2.5% (HR 0.975; 95% CI 0.958–0.994) for diabetes, 4.3% (HR 0.957; 95% CI 0.932–0.983) for asthma and 1.8% (HR 0.982; 95% CI 0.971–0.992) for all-cause mortality. There was no statistically significant association between baseline per cent predicted FEV1 and future risks of myocardial infarction (HR 0.987; 95% CI 0.970–1.004) and hypertension (HR 0.998; 95% CI 0.992–1.005). Consistent results were observed for the Fine–Gray sub-distribution hazard model. Conclusion: Our data suggest that lower per cent predicted FEV1 values at baseline were significantly associated with higher future risks of diabetes, asthma and all-cause mortality. These data suggest that lower FEV1 % predicted values at baseline are significantly associated with a higher future risk of diabetes, asthma and all-cause mortality https://bit.ly/3hVinnB